2017
DOI: 10.1093/eurpub/ckx085
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effectiveness of nudging to increase fruit and vegetable choice

Abstract: BACKGROUND: Nudging refers to interventions that organize the choice architecture in order to alter people's behaviour in a predictable way without forbidding any options or significantly changing their economic incentives. As a strategy to encourage healthy behaviour, nudging can serve as a complement to health education. However, the empirical evidence regarding the effectiveness of nudging as a way to influence food choice remains contradictory. To address this issue, a systematic review and meta-analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 37 publications
(38 reference statements)
6
114
0
4
Order By: Relevance
“…While the specific mechanisms differ among the surveyed studiesfrom changing the effort to obtain food, the perception of healthiness and quantity, and the sensation of foods (i.e., flavours or oral processing) before or during a mealmost results suggest that such interventions could effectively alter food choices. Studies reviewing changes in food positioning, dishware, portion size, and food variety find a meaningful influence on food choices (Broers et al 2017;Bucher et al 2016;Holden et al 2016;Hollands et al 2015;Roy et al 2015;Wadhera and Capaldi-Phillips 2014;Zlatevska et al 2014). Still, a relevant number of reviews could not support such an overall conclusion (Libotte et al 2014;Robinson et al 2014b;Skov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While the specific mechanisms differ among the surveyed studiesfrom changing the effort to obtain food, the perception of healthiness and quantity, and the sensation of foods (i.e., flavours or oral processing) before or during a mealmost results suggest that such interventions could effectively alter food choices. Studies reviewing changes in food positioning, dishware, portion size, and food variety find a meaningful influence on food choices (Broers et al 2017;Bucher et al 2016;Holden et al 2016;Hollands et al 2015;Roy et al 2015;Wadhera and Capaldi-Phillips 2014;Zlatevska et al 2014). Still, a relevant number of reviews could not support such an overall conclusion (Libotte et al 2014;Robinson et al 2014b;Skov et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the strength of the positioning effect is found to be heterogeneous and to depend on the type of manipulation and the magnitude of the change (Bucher et al 2016;Wisdom et al 2010). Considering only studies altering the position, the meta-analysis by Broers et al (2017) showed an overall positive effect of preferred positioning on fruit and vegetable choice (d = 0.39).…”
Section: Positioningmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, nudging strategies has been introduced to change people's diet-related behaviour (Boyland & Halford, 2013) and motivate them to make a healthier food choice (Broers, De Breucker, Van den Broucke, & Luminet, 2017;Bucher et al, 2016;Stroebele-Benschop, Depa, & de Castro, 2016). There is reason to believe that nudging could be applied to influence older people's food choice and promote their' healthy eating (Hansen, Skov, & Skov, 2016).…”
Section: Introductionmentioning
confidence: 99%